Evaluation of microcrack formation after root-end preparation with two different types of ultrasonic retrotips and conventional bur: A stereomicroscopic study - Dilshad Kersi Mandviwala; Vineet Suresh Agrawal; Sonali Vinod Kapoor (Wolters Kluwer Medknow Publications, 2021)
Introduction: The aim of this in vitro study is to evaluate and compare the root-end cavities for the presence of microcracks after cavity preparation using two different ultrasonic (US) retrotips and conventional bur. Materials and Method: Thirty single-rooted teeth were instrumented and obturated. Three millimeters of apices were resected. Retrograde Class I cavities 3 mm deep were prepared on resected surfaces of ten teeth with diamond-coated US retrotip (Group 1), ten teeth with zirconium-nitride-coated US retrotip (Group 2), and ten teeth with conventional bur (Group 3). The root-end surfaces were examined under a stereomicroscope and the resected root surfaces were evaluated for the presence of microcracks on microphotographs. Results: Statistically significant difference was detected between diamond-coated and zirconium-nitride-coated US retrotips and also significant difference was detected when the same were compared with conventional bur for the presence of microcracks. Conclusion: Within the limitations of the study, it can be concluded that both zirconium-nitride- and diamond-coated retrotips produce more dentinal crack formation compared to conventional bur, but none of them produce a complete crack. Moreover, the diamond-coated retrotips produce less debris formation and minimal dentinal crack compared to zirconium-nitride-coated retrotips.